Reducing Surgical Infections and Implant Costs via a Novel Paradigm of Enhanced Physician Awareness. Issue 5 (24th May 2017) - Agarwal, Nitin; Agarwal, Prateek; Querry, Ashley; Mazurkiewicz, Anna; Whiteside, Brittany; Marroquin, Oscar C; Koscumb, Stephen F; Wecht, Daniel A; Friedlander, Robert M
Abstract: BACKGROUND: Studies have demonstrated that physicians are often unaware of prescription drug, laboratory, diagnostic, and surgical supply costs. OBJECTIVE: To investigate the effects of increased physician awareness on infection incidence and surgical device cost containment. METHODS: Within our institution, physicians were informed of individual, independently adjudicated, craniotomy and ventricular shunt infection incidence and rankings among peers, after which a protocol aimed at reducing skin bacterial burden was implemented for craniotomies. Physicians were also made aware of the costs for shunts and dural substitutes as well as available alternatives. RESULTS: The combined craniotomy and ventricular shunt infection incidence significantly decreased by 37.5% from 3.2% over May 2011 to April 2015 (132 infections/4137 procedures) to 2.1% over May 2015 to April 2016 (26 infections/1250 procedures; P = .041). The average annual cost savings was $234 175 from preventing postoperative craniotomy infections and $121 125 from preventing postoperative ventricular shunt infections. Total supply costs of ventricular shunts significantly decreased by 26% from $2345 per procedure in fiscal year 2015 to $1747 per procedure in fiscal year 2016 ( P < .001). Total supply cost of dural grafts significantly decreased by 54% from $191 per procedure in fiscal year 2015 to $88 per procedure in fiscal year 2016 ( P < .001). In total, all initiatives in this study resulted in an estimated annual savings of $567 062. CONCLUSION: Physician awareness of outcomes and costs resulted in increasing the quality of care, while at the same time reducing the cost.